AB0851 OBESITY AND RISK OF FRACTURE: DEPENDS ON THE BODY MASS INDEX AND TYPE OF FRACTURE. (June 2019) - Rosas, Jose; Cano, Catalina; Pons, Ana; Ivars, Estíbaliz; Senabre-Gallego, José Miguel; Soler, Gregorio Santos; Salas-Heredia, Esteban; Bernal-Vidal, José Antonio; García-Gómez, José Alberto; Barber, Xavier; ,
Abstract : Objectives: To know the impact of obesity on the risk of fracture. Methods: Observational study, during 2010-2018, of patients referred for bone densitometry (BMD), to the Bone Densitometry Unit of Rheumatology. BMD performed by Rheumatology nursing, collect several data (age, gender); osteoporosis (OP) risk factors: age of menopause, smoking and current alcohol intake, hip fracture parents, body mass index (BMI), diseases-drugs that reduce bone mass, fractures, treatment; BMD in lumbar spine (LS), femoral neck (FN); FRAX with BMD. BMI result was as WHO recommendations in kg/m 2 : Normal: 18.5-24.99; Obesity: ≥30; type I: 30-34.99, type II: 35.39.99, type III: ≥40. Results: A first BMD in 6.943 postmenopausal women was done. 2.196 (32%) had normal BMI, low weight (BMI <18.5 kg/m 2 ) 103 (1.5%) patients, overweight (BMI 25-29.99 kg/m 2 ) 2.643 (38%) and obesity 2.001 (29%). Obesity (BMI ≥30 kg/m 2 ) vs normal BMI, are older (65±13 vs 61±13, p=0.005), lower current smokers (12% vs 27%) P <0.0001), more treated for OP (37% vs 29%, p=0.002), higher percentage of fractures (44% vs 29%), especially distal radius (DR) (30% vs 11%), p<0.001) and vertebral (19% vs 7%, p=0.002), lower mean T score in LS (-1.1±1.5 vs 1.8±1.5, p <0.0001) and FN (-1.1±1.5 vs -1.6 ± 1.5, p<0.0001) and lower mean FRAX hip fracture with BMD (1.9±3.6 vs 2.4±3.6, p <0.0001). In table, obesity groups are compared with normal BMI. Conclusion: In postmenopausal women referred for BMD, obese women vs normal BMI are 1. Older. 2. Overall, with higher percentage of fractures. 3. But, women with BMI≥ 40 kg/m 2 do not have a higher overall percentage of fracture, except in DR. Acknowledgement: The study was supported with a research grant from the Association for Research in Rheumatology of Marina Baixa (AIRE-MB) Disclosure of Interests: Jose Rosas Consultant for: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Speakers bureau: Abbvie, Amgen, Bristol, Janssen, Lilly, Merck Sharp & Dohme, Pfizer, UCB Pharma, Catalina Cano: None declared, Ana Pons: None declared, Estíbaliz Ivars: None declared, José Miguel Senabre-Gallego: None declared, Gregorio Santos Soler: None declared, Esteban Salas-Heredia: None declared, José Antonio Bernal-Vidal: None declared, José Alberto García-Gómez: None declared, Xavier Barber: None declared